Stigma experienced by persons infected with COVID-19: An exploratory study from India - Berigai Parthasarathy Nirmala; Manoj Kumar Sharma; Anish V Cherian; Pallerla Srikanth; S Mallesh; Kanmani T Raju (Wolters Kluwer Medknow Publications, 2023)
Background: The COVID-19 pandemic had spread throughout the world very quickly and had impacted all spheres of human life. Person infected with COVID-19 (PIwC-19) faces issues not only with physical health but also with their psychological health and the mental health needs were found to be significant. The stigma and discrimination toward the disease were also extended to the near and dear ones of PIwC-19. The current study is an attempt to explore the stigma experienced by the PIwC-19. Materials and Methods: The study used an exploratory research method to assess the stigma experienced by the PIwC-19. The list of PIwC-19 was obtained from the Department of Health and Family Welfare, Karnataka. The study was conducted in South Bangalore after segregating the list. PIwC-19 between ages of 18 and 60 years was included in the study. The Explanatory Model Interview Catalogue Scale was used to assess the stigma and an interview guide developed by researchers was used to assess the manifestations of stigma. Results: One-third of the subjects were male (n = 105), studied up to higher secondary (n = 101), married (n = 127), and employed (n = 126), and the mean age of the participants in the study is 39.21 ± 11.04 (years). Many of the participants (62%), (n = 93) have reported severe levels of the stigma. Conclusion: It is evident from the current study findings that PIwC-19 experienced moderate-to-severe levels of stigma. The current study has explored the various causes, forms, and consequences of stigma in a small population. Stigma was manifested in family, community, and at workplace, recreational places, and peer groups.